ESG disclosure and technological innovation capabilities of the Chinese listed companies - Mohammad Abedin (Research in International Business and Finance, 2023)
The main objective of this study is to explore how ESG disclosure effectively promotes technological innovation capabilities (TIC) and also in different industries (green vs. high-tech). Further, examine the role of financing constraint (FC) in the relationship between the ESG disclosure and TIC. We employed the panel regression model, Causal step approach, Bootstrap mediation effect test, 2SLS, and GMM model. We used Bloomberg’s ESG disclosure score of China’s A-share listed companies from 2011–2019 (1); we found that the ESG disclosure has a significant relationship with corporate innovation indicators (OTI, STI, NSTI) and play a significant role in promoting TIC at different levels of corporate innovation (2) ESG disclosure of non-green (high-tech) industry is more effectively promote TIC than green (non-high tech) industry (3) ESG disclosure can promote corporate innovation by reducing the level of corporate financing constraints, and FC has a partial intermediary role between ESG and TIC.